Effect of time-of-day-specific strength training on maximum strength and EMG activity of the leg extensors in men - Sedliak, M.; Finni, T.; Peltonen, J.; Häkkinen, K. (Journal of Sports Sciences, 2008)
In this study, we examined the effects of time-of-day-specific strength training on maximum strength and electromyography (EMG) of the knee extensors in men. After a 10-week preparatory training period (training times 17:00-19:00 h), 27 participants were randomized into a morning (07:00-09:00 h, n = 14) and an evening group (17:00-19.00 h, n = 13). Both groups then underwent 10 weeks of time-of-day-specific training. A matched control group (n = 7) completed all testing but did not train. Unilateral isometric knee extension peak torque (MVC) and one-repetition maximum half-squat were assessed before and after the preparatory training and after the time-of-day-specific training at times that were not training-specific (between 09:00 and 16:00 h). During training-specific hours, peak torque and EMG during MVC and submaximum isometric contraction at 40% MVC were assessed before and after the time-of-day-specific training. The main finding was that a significant diurnal difference (P < 0.01) in peak torque between the 07:00 and 17:00 h tests decreased after time-of-day-specific training in the morning group but not in the evening or control groups. However, the extent of this time-of-day-specific adaptation varied between individuals. Electromyography during MVC did not show any time-of-day-specific adaptation, suggesting that peripheral rather than neural adaptations are the main source of temporal specificity in strength training.